1982
DOI: 10.1037/0022-006x.50.5.770
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between the Luria-Nebraska and the Halstead-Reitan Neuropsychological Batteries: Effects of partialing out education and postmorbid intelligence.

Abstract: This comment discusses the relationship between the Halstead-Reitan and Luria-Nebraska Neuropsychological Batteries, examining the role of intelligence and related factors in this relationship. The problems with using a postmorbid IQ as a covariate in assessing the relationship between two neuropsychological tests are discussed. Such a procedure corrects for degree and severity of brain injury in addition to premorbid levels of intelligence. Alternative measures such as education are suggested, which can be em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Test for the Luria-Nebraska Neuropsychological Battery (adult form) is a 15-item assessment instrument used to predict overall performance on the full-length battery (Golden, 1987). The full-length LNNB is a muld-dimensional assessment instrument that assesses neuropsychological functioning in sensorimotor, perceptual and cognitive domains (Golden, Gustavson & Ariel, 1982). The result of the screening test administration is used as a probabilisdc indicator of the performance classification ("normal" vs. "clinically impaired") that would be obtained if the fiall-length 269-item battery were to be administered.…”
Section: Screening Test For the Luria-nebraska Neuropsychological Batmentioning
confidence: 99%
“…Test for the Luria-Nebraska Neuropsychological Battery (adult form) is a 15-item assessment instrument used to predict overall performance on the full-length battery (Golden, 1987). The full-length LNNB is a muld-dimensional assessment instrument that assesses neuropsychological functioning in sensorimotor, perceptual and cognitive domains (Golden, Gustavson & Ariel, 1982). The result of the screening test administration is used as a probabilisdc indicator of the performance classification ("normal" vs. "clinically impaired") that would be obtained if the fiall-length 269-item battery were to be administered.…”
Section: Screening Test For the Luria-nebraska Neuropsychological Batmentioning
confidence: 99%
“…While the composite proxy variable in this study produced slightly smaller path coefficients to depression and from the physical health construct, it did show the ability to capture When scientific problems call for an estimate of an underlying construct, and this construct is not adequately represented by a proxy variable, then investigators must concede that their parameter estimates may be biased. Golden et al (1982), estimating the relationship between the intelligence of braindamaged patients and degree of brain damage, determined that measures of predamage intelligence were required for adequate statistical control. In the absence of any possible measure of predamage intelligence, the authors used predamage education as a proxy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent issue of this journal, Chelune (1982) commented that whereas the subtests of the Luria-Nebraska (LNNB) and Halstead-Reitan (HRB) neuropsychological batteries appear to be highly intercorrelated, as reported in Golden et al (1981), much of this apparent relationship could be accounted for by their common overlap with Wechsler Adult Intelligence Scale (WAIS) IQ scores. In reply, Golden, Gustavson, and Ariel (1982) suggested that examination of the relationship between the LNNB and HRB with their overlap with postmorbid Wais scores partialed out, understimates the "real ability of the Halstead-Reitan and Luria-Nebraska batteries to predict one another within a brain-injured population" (p. 770). They base their assertion on the fact that "WAIS scores are strongly related to the presence and degree of impairment caused by brain damage" and that "correcting" for the effects of postmorbid intelligence essentially partials out the effects of brain damage, "the very thing the [neuropsychological] tests are set to measure" (p. 770).…”
mentioning
confidence: 99%